Some notes about mythological myths - Mehriniso Rizayeva (International Consortium of Education and Culture Research Studies, 2019)
This paper makes analyses of the myth and magic world of the creative heroes, sculptors, and heroic titans has probably played an important role in the formation of epic heroes, folk heroes, and even the primary function during the development of artistic thought.